Efficacy of targeted drugs in germ cell cancer cell lines with differential cisplatin sensitivity - Schaffrath, Judith; Schmoll, Hans-Joachim; Voigt, Wieland; Müller, Lutz P.; Müller-Tidow, Carsten; Müller, Thomas (PLOS ONE, 2017)
Testicular germ cell tumors (TGCTs) are the most common malignancies in men between the age of 15 and 35. Although cisplatin-based chemotherapy is highly effective in advanced disease, approximately 20% of patients have an unfavorable prognosis due to primary or acquired cisplatin resistance. For these patients, new therapeutic options are urgently needed. In numerous tumor entities, combinations of monoclonal antibodies or kinase inhibitors with chemotherapy exerted promising preclinical or clinical results, which have led to new treatment concepts. This prompted us to investigate the activity of different targeted agents alone or in combination with cisplatin in a panel of TGCT cell lines. Methods The in vitro activity of kinase inhibitors targeting mTOR (RAD001), EGFR, HER2/neu, VEGFR (AEE788) and IGF-1R (AEW541) alone or in combination with cisplatin was tested in the cisplatin sensitive TGCT cell lines H12.1 and GCT72 as well as in the resistant cell lines H12.1RA, H12.1D, 1411HP and 1777NRpmet using the sulforhodamin-B-(SRB)-cytotoxicity-assay. To evaluate the activity of the kinase inhibitors, western blot analysis of the targeted receptors and their phosphorylated state was performed before and after exposure to each substance. Results The different kinase inhibitors demonstrated significant cell growth inhibition in both cisplatin sensitive and resistant cell lines. The examined cell lines showed different protein expression levels of the targeted receptors. However there was no correlation between the targeted receptor expression and phosphorylation level and the antiproliferative effect of the respective agent. Furthermore, the combination of cisplatin and the kinase inhibitors exerted both additive and antagonistic effects in the studied cell lines. Conclusion Our data suggest potential activity of the investigated kinase inhibitors in both cisplatin sensitive and resistant TGCT cell lines as a single agent. However, when combined with cisplatin they did not demonstrate any promising ability to overcome cisplatin resistance in TGCTs.
Gesehen am 26.11.2024